The quest for unligated oxaphosphiranes with phosphorus in different coordination numbers. Issue 10 (5th January 2023) - Faßbender, Jan; Volk, Niklas; García Alcaraz, Antonio; Balasubramaniam, Selvakumar; Espinosa Ferao, Arturo; Streubel, Rainer
Abstract : The first oxaphosphirane I  has been synthesized. Reactions with borane (II ) and oxidizing reagents (II,  III ) are reported, together with theoretical studies providing insight into ring strain energy, oxidation pathways and ring isomerization. Abstract : After more than 160 years of oxirane (epoxide) chemistry, the first derivative of a phosphorus analogue, namely oxaphosphirane, has been synthesized. Reactions with borane sulfane, a peroxy compound and elemental sulfur, as well as tetra-chloro- ortho -benzoquinone (TOB) reveal a significant destabilization upon increasing the coordination number at phosphorus from σ 3 to σ 4, thus somehow supporting previous reports on such fleeting species. Theoretical studies provide insight into ring strain energy, ring/ring interconversion and the oxidation pathways.